DUKUNGAN KADER DAN KELUARGA DENGAN PEMANFAATAN POS PEMBINAAN TERPADU PENYAKIT TIDAK MENULAR - Handono Fatkhur Rahman (Jurnal Ilmiah Kesehatan Media Husada, 2020)
Posbindu is a form of early detection of risk factors carried out continuously and continuously. Prevention of non-contagious disease is a combination of efforts for independent maintenance initiatives by officers, the community, and the individuals concerned and health promotion policies are then implemented intensively. The purpose of the study was to analyze the relationship between cadre and family support with the use of integrated non-communicable disease PTM posts in the Tlogosari Community Health Center Tlogosari District work area. The research design with a cross sectional research approach with a total sample of 221 respondents who met the inclusion criteria with judgment sampling technique.Then analyzed by chi-square test. The results of the study showed that out of 221 respondents, most of the cadre support used Posbindu as many as 119 respondents (53.8%) and most of the families who used Posbindu were 119 respondents (53.8%). Statistical test results with Chi Square test obtained ρ = 0.00, so that ρ <0.05, interpreted that there is a relationship between cadre support and the use of Posbindu, likewise there is a family relationship with the use of Posbindu by obtaining ρ = 0.00, so ρ < 0.05. It was concluded that there was support from cadres and families with the use of Posbindu in the Tlogosari Community Health Center and it was hoped that the community would really use Posbindu PTM as the smallest health facility in the community to prevent the increase in the incidence of non-communicable diseases.